Multi-Scale Contact Localization and Dynamic Instability Related to Brake Squeal - Van-Vuong Lai; Igor Paszkiewicz; Jean-François Brunel; Philippe Dufrénoy (Lubricants, 2020)
Friction-induced vibrations (brake squeal) produced during braking applications have been one of the major problems in the transportation for many years. It can be the most troublesome for passengers because of its high frequency and acoustic pressure. The role of frictional contact surface geometry on the occurrence of squeal was investigated recently by some researchers. However, it has never been systematically studied at different scales simultaneously. Contact localizations are induced on the one hand by macro effects such as thermal dilatation (macroscopic scale) and on the other hand, by the heterogeneity of third body (tribolayer) generated by friction (mesoscopic scale). The aim of this paper is to investigate the effect of contact localization at both scales through stability analysis on a simplified pad on disc system. The model has been developed numerically by the finite element method (FEM) to introduce a non-uniform contact at macroscopic and mesoscopic scales. The results showed a strong dependency between squeal frequencies and effective contact zone at macroscopic and mesoscopic scales for the investigated configuration. Especially, it is found that squeal frequencies depend on the contact area at a macroscopic scale whereas the probability of occurrence of squeal frequency strongly relies on mesoscopic contact distribution.